2022
DOI: 10.1155/2022/1863519
|View full text |Cite
|
Sign up to set email alerts
|

The Quest for Outpatient Mastectomy in COVID-19 Era: Barriers and Facilitators

Abstract: Background. The rate of inpatient mastectomies remains high despite multiple studies reporting favourably on outpatient mastectomies. Outpatient mastectomies do not compromise quality of patient care and are more efficient than inpatient care. The objective of this study was to evaluate the feasibility of outpatient mastectomy. Materials and Methods. Implementation of an outpatient mastectomy program was evaluated in a retrospective study. All patients who underwent mastectomy between January 2019 and Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 29 Cordeiro et al (2016) reported an average estimated saving of $4000 per patient with the transition from an overnight stay to same-day discharge after major breast cancer surgery. 20 , 25 Factors that may be considered potential barriers to same-day discharge in major breast cancer surgery included bilateral procedures, 30 obesity, and age. 25 Failed same-day discharge may be attributed to postoperative nausea, vomiting, and inadequate pain control.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Cordeiro et al (2016) reported an average estimated saving of $4000 per patient with the transition from an overnight stay to same-day discharge after major breast cancer surgery. 20 , 25 Factors that may be considered potential barriers to same-day discharge in major breast cancer surgery included bilateral procedures, 30 obesity, and age. 25 Failed same-day discharge may be attributed to postoperative nausea, vomiting, and inadequate pain control.…”
Section: Discussionmentioning
confidence: 99%